Normal and abnormal development of visual functions in children - Kozma, Petra; Kovács, Ilona; Benedek, György (Acta Biologica Szegediensis, 2001)
The human visual system goes through substantial changes during the first few months of postnatal life. The development of visual functions and structures occurs at different times and different rates. It has been a generally held belief that the development of visual functions and their critical period come to an end early in life. Most of the developmental data confirm this theory, although the findings sometimes are contradictory. Thus, our knowledge concerning visual development does not seem to be complete. The determination of exact timing of the different visual functions is relevant in children since a proved extended maturational timeframe can promote the trial of enhancement of visual abilities at a later age, up to puberty or beyond. There have already been suggestions for an extended developmental time span for some of the visual functions. Here we review the most relevant data with reference to the normal development of the eye, visual functions and visual pathways found in the literature and provide further evidence for the maturation and plasticity of visual functions after the age of 5 years.